The mechanism underlying the relationship between the spiritual struggles and life satisfaction of Polish codependent individuals participating in Al-Anon – pilot study - Wnuk, Marcin (Journal of spirituality in mental health, 2023)
Codependency is a serious mental, emotional, social, and physical problem. Little is known about the spiritual mechanism of recovery among codependent individuals participating in Al-Anon self-help groups. The aim of this study was to verify whether spiritual struggles are indirectly through spiritual growth and hope, related to life satisfaction of codependent individuals. The achieved results confirmed the indirect effect of spiritual struggles on life satisfaction through the spiritual growth and hope of codependent individuals participating in Al-Anon. The research confirmed the mechanism underlying the relationship between spiritual struggles and the life satisfaction of codependent individuals participating in Al-Anon.